THE INFLUENCE OF SUKSES BER-KB COUNSELING TOOL TO KNOWLEDGE OF ORAL CONTRACEPTIVE ACCEPTORS AT PHARMACIES IN MALANG - Pramestutie, Hananditia R; Illahi, Ratna K; S Perdanastuti, Hidayah; L Hariadini, Ayuk; H, Lathifah (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The use of oral contraceptive requires specific instructions. Pharmacist, as a part of healthcare provision, is able to counsel their clients about the proper use of oral contraceptive to be successful in family planning program. Pharmacist must be able to explain what acceptors should do if she misses pills and possible side effects because side effects are the most common reasons for women discontinuing combined oral contraceptive (COC). Therefore, counseling is an important part of family planning service. To provide more effective counseling, this study used Sukses Ber-KBâ€ computer application as a counseling tool. We aimed to determine the effect of this tool on improving the knowledge of oral contraceptive acceptors interviewed at pharmacies in Malang. Methods: Pharmacy selection was done by cluster random sampling based on the five districts of Malang, while acceptors were selected using a purposive sampling method, resulting in 106 COC acceptors. This study comprises pre-experimental research (one group pretest-posttest) with a cross-sectional study design, the analysis using Wilcoxon test. Results: The analysis of the results using a Wilcoxon test showed a significance value of 0 (p<0.05). The study sought to determine change in the contraceptive users knowledge scores about COC s following counseling with the Sukses Ber-KB counseling tool. The results also showed 105 positive score changes (increased knowledge) and 1 tie. Conclusion: It is concluded that the use of the Sukses Ber-KB counseling tool showed significant increase in the users’ knowledge about oral contraceptives with p<0.05.